High RSF1 protein expression is an independent prognostic feature in prostate cancer. (3rd March 2020) - Höflmayer, Doris; Hamuda, Moslim; Schroeder, Cornelia; Hube-Magg, Claudia; Simon, Ronald; Göbel, Cosima; Hinsch, Andrea; Weidemann, Sören; Möller, Katharina; Izbicki, Jacob R.; Jacobsen, Frank; Mandelkow, Tim; et al.
Abstract: Background: Remodelling and spacing factor 1 (RSF1) is involved in the regulation of chromatin remodelling and represents a potential therapeutic target. High RSF1 expression has been linked to adverse tumour features in many cancer types, but its role in prostate cancer is uncertain. Methods: In this study, RSF1 expression was analysed by immunohistochemistry on a tissue microarray with 17, 747 prostate cancers. Results: Nuclear RSF1 staining of 16, 456 interpetable cancers was considered strong, moderate, weak and negative in 25.2%, 48.7%, 5.3% and 20.8% of cancers respectively. Positive RSF1 expression was associated with advanced tumour stage, high Gleason grade, lymph node metastasis ( p < .0001 each), early biochemical recurrence ( p < .0003) and more frequent in the ERG positive than in the ERG negative subset (88% versus 71%; p < .0001). Subset analysis revealed, that associations between RSF1 expression and unfavourable tumour phenotype and PSA recurrence were present in both subgroups but stronger in the ERG negative than in the ERG positive subset. The univariate Cox proportional hazard ratio for PSA recurrence-free survival for strong versus negative RSF1 expression was a weak 1.60 compared with 5.91 for the biopsy Gleason grade ≥4 + 4 versus ≤3 + 3. The positive association of RSF1 protein detection with deletion of 3p13, 10q23 (PTEN), 12p13, 16q23, and 17p13 ( p < .0001 each) suggest a role of high RSF1 expression in the development of genomic instability. Conclusion: In summary, the results of our study identify RSF1 as an independent prognostic marker in prostate cancer with a particularly strong role in ERG negative cases.